2011
DOI: 10.1002/pbc.22994
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of attention‐deficit/hyperactivity disorder in long‐term survivors of childhood leukemia

Abstract: Background Survivors of childhood acute lymphoblastic leukemia (ALL) sometimes have clinical features that suggest Attention-Deficit/Hyperactivity Disorder (ADHD), though few studies have examined specific symptoms in survivors. Procedure Long-term survivors of childhood ALL (n=161) received a neurological examination, while parents completed rating scales to establish formal criteria for ADHD. Symptom profiles were generated and compared across demographic and treatment characteristics, as well as medical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…ADHD had a reported prevalence of 9.0-10.5% in survivors of childhood leukemia or brain tumor. 36,37 These rates are similar to those in the general population. However, another study reported that the prevalence of ADHD in childhood cancer may be lower than in the general population 38 for several reasons.…”
Section: Discussionsupporting
confidence: 78%
“…ADHD had a reported prevalence of 9.0-10.5% in survivors of childhood leukemia or brain tumor. 36,37 These rates are similar to those in the general population. However, another study reported that the prevalence of ADHD in childhood cancer may be lower than in the general population 38 for several reasons.…”
Section: Discussionsupporting
confidence: 78%
“…Comparison of participants and non-participants is already published [15]. There was no difference between participants and non-participants ( n =270) in gender distribution ( p =0.89), age at ALL diagnosis ( p = 0.99), ALL risk group ( p =0.53), B or T cell lineage ( p =0.94), high dose methotrexate ( p =0.26) or intrathecal methotrexate use ( p =1.00), prednisone ( p =0.98) or dexamethasone use ( p = 0.28), and treatment with cranial radiation ( p =0.29).…”
Section: Resultsmentioning
confidence: 99%
“…As previously published [15], participants responded to an 18-item questionnaire probing symptoms of attention deficit hyperactivity disorder consistent with the Vanderbilt Attention-Deficit Hyperactivity Disorder Parent Rating Scale [16]. DSM-IV criteria were then applied to determine if a participant had attention deficit, hyperactivity, or both.…”
Section: Methodsmentioning
confidence: 99%
“…More than one half of survivors (54%) received intrathecal methotrexate, cranial radiation, or both and treatments with cranial radiation and/or intrathecal methotrexate were specific risk factors for depression/anxiety, attention deficit, antisocial behaviors, and diminished social competence. Attention problems are commonly reported in these patients (up to 25.5% of the survivors), but the rate of patients meeting the full criteria for ADHD is only of 10.5%-just slightly higher than the reported rate in the general population (Krull et al, 2011). Also, similar rates of ADHD were seen in boys and girls, and especially in the patients that have received cranial radiation therapy.…”
Section: Behavioral Disturbances and Attention Deficit Syndromesmentioning
confidence: 54%
“…In addition, many survivors also have multiple behavioral symptoms suggestive of attention deficit/hyperactivity disorder (ADHD) (Krull et al, 2011). These abnormalities are assessed by behavioral ratings-especially from the family and classroom teachers.…”
Section: Behavioral Disturbances and Attention Deficit Syndromesmentioning
confidence: 99%